1991
DOI: 10.1021/es00020a015
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of mixed-organic wastes by microbial consortia in continuous-recycle expanded-bed bioreactors

Abstract: Microbial consortia enriched from subsurface sediments contaminated with chlorinated hydrocarbons proved capable of degrading mixed-organic wastes. Methane and/or propane as foodstock enabled aerobic mineralization of greater than 20 mg L"1 trichloroethylene (TCE) plus 1 mg L"1 vinyl chloride, benzene, and toluene in cell suspension or bioreactor experiments. The microbial consortia degraded 80-95% of TCE at 20 mg L"1 within 5 days in continuous-recycle expanded-bed bioreactors requiring 50-100 mol of foodstoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
27
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 9 publications
4
27
0
Order By: Relevance
“…The trichloroethylene degradation rates (in the presence of mixed waste) observed in this study are almost an order of a magnitude higher than those reported earlier from this laboratory (14). Decreased rates of trichloroethylene observed in reactor 2 after 8 d agreed well with other studies (12,13).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The trichloroethylene degradation rates (in the presence of mixed waste) observed in this study are almost an order of a magnitude higher than those reported earlier from this laboratory (14). Decreased rates of trichloroethylene observed in reactor 2 after 8 d agreed well with other studies (12,13).…”
Section: Resultssupporting
confidence: 91%
“…These studies have reported a decrease in trichloroethylene degradation rates as concentrations of trichloroethylene decreased to approx 500 #g/L. The degradation of aromatic compounds, like benzene, toluene, and xylene, was also found to be faster than found earlier in this (14). The presence of methane and propane did not seem to affect degradation of aromatics, like benzene, toluene, and xylene.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…PCE while not degraded by methanotrophs, is easily degraded to TCE by anaerobic reductive dechlorination. This was demonstrated to occur in the large number of anaerobic microniches created in the subsurface by the biostimulation of methanotrophs (Phelps et al, 1990;Enzien et al, 1994;Pfiffner et al, 1997;Hazen, 1999) in bulk aerobic environments. Thus stimulation of methanotrophs will result in significant biodegradation of PCE.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous compounds such as chemical residues, organic matter, and fouling of tiny sizes are hardly retained by a filter medium, being, in most of cases, responsible for levels of toxicity commonly detected in drinking water (Mallevialle, 1996). A possible way to enhance removal effectiveness is to combine the separation process with the presence of living organisms, biopolymers or natural biofilms coatings in the filter cake, promoting *Corresponding author interactions at molecular level (Bryers et al 1990;Phelps et al 1990;Weber-Shirk and Dick, 1997). The biopurification process is a very desirable clean-up technology employing active elements for in-situ removal, not only of bacteria and viruses but also for the degradation of chemical residues such as fertilizer and herbicide contaminants in water and soil (Bollag, 1996).…”
mentioning
confidence: 99%